Effect of Non-Steroidal Anti-Inflammatory Drugs on Bone Healing - Jessica Cottrell; J. Patrick O'Connor (MDPI AG, 2010)
Nonspecific and COX-2 selective nonsteroidal anti-inflammatory drugs (NSAIDs) function by inhibiting the cyclooxygenase isoenzymes and effectively reduce pain and inflammation attributed to acute or chronic musculoskeletal pathologies. However, use of NSAIDs as an analgesic is thought to negatively contribute to bone healing. This review strived to provide a thorough unbiased analysis of the current research conducted on animals and humans regarding NSAIDs and their effect on bone healing. Specifically, this review discusses the role of animal models, dosing regiments, and outcome parameters when examining discrepancies about NSAIDS and their effects on bone regeneration. The role of COX-2 in bone regeneration needs to be better defined in order to further elucidate the impact of NSAIDs on bone healing.